Coruption Crime Prevention in handling illegal logging By Batulante KPHP - Muhammad Ikbal; Mirza Amelia (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2019)
Corruption is a very massive act, because it almost happens in all aspects of government activities. Such as the handling of illegal logging is very sensitive to the practice of corruption. Illegal logging is only a small proportion of corruption. Therefore this research is looking for ways of Batulante KPHP in handling corruption in tackling illegal logging, and looking for factor that cause obstacles in handling corruption in the enforcement of illegal logging and look for factor that cause obstacles in handling corruption in the enforcement of illegal logging. the method used in this study uses normative and empirical researc methods in which the data collected is assessed qualitatively and supports quantitative data. The analysis in this study uses deductive analysis. This research aims to provide a renewal or add to a theory in preventing the occurrence of corruption, especially in the field of forest protection as well as providing advice and solutions in tackling corruption against illegal logging.